Assessment of the societal and individual preferences for fertility treatment in Australia: study protocol for stated preference discrete choice experiments. Issue 2 (14th February 2018) - Botha, Willings; Donnolley, Natasha; Shanahan, Marian; Chambers, Georgina M
Abstract : Introduction: In Australia, societal and individual preferences for funding fertility treatment remain largely unknown. This has resulted in a lack of evidence about willingness to pay (WTP) for fertility treatment by either the general population (the funders) or infertile individuals (who directly benefit). Using a stated preference discrete choice experiment (SPDCE) approach has been suggested as a more appropriate method to inform economic evaluations of fertility treatment. We outline the protocol for an ongoing study which aims to assess fertility treatment preferences of both the general population and infertile individuals, and indirectly estimate their WTP for fertility treatment. Methods and analysis: Two separate but related SPDCEs will be conducted for two population samples—the general population and infertile individuals—to elicit preferences for fertility treatment to indirectly estimate WTP. We describe the qualitative work to be undertaken to design the SPDCEs. We will use D-efficient fractional experimental designs informed by prior coefficients from the pilot surveys. The mode of administration for the SPDCE is also discussed. The final results will be analysed using mixed logit or latent class model. Ethics and dissemination: This study is being funded by the Australian National Health and Medical Research Council (NHMRC) project grant AP1104543 and has been approved by the University of New South Wales Human Research Ethics Committee (HEC 17255) and a fertility clinic's ethics committee. Findings of the study will be disseminated in peer-reviewed journals and presented at various conferences. A lay summary of the results will be made publicly available on the University of New South Wales National Perinatal Epidemiology and Statistics Unit website. Our results will contribute to the development of an evidence-based policy framework for the provision of cost-effective and patient-centred fertility treatment in Australia.